Characteristics and principles of humanism in Kurdish story in East Kurdistan - Mohammed Ghafur, Rezan; Hussein Bakir, Hemdad (Zanco Journal of Human Sciences, 2023)
This study tagged with (Characteristics and principles of humanism in Kurdish story in East Kurdistan) it consists of an introduction and two main chapters. We covered the characteristics and principles in the first chapter: the concept, freedom, love, tolerance, peace, justice and equality, love of the land and country, women’s rights….and several other principles of humanism. The second chapter, which has revealed the aspects of humanity in the Kurdish story in eastern Kurdistan, finally, there are the results that have consistently reached us.